Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Sonawane, Prashant; Singh, Somesh; Kumari, Uma; Ruby; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2013)
Triterpenoid saponins are the class of secondary metabolites, synthesized via isoprenoid pathway. Oxidosqualene cyclases (OSCs) catalyzes the cyclization of 2, 3-oxidosqualene to various triterpene skeletons, the first committed step in triterpenoid biosynthesis. A full-length oxidosqualene cyclase cDNA from Bacopa monniera (BmOSC) was isolated and characterized. The open reading frame (ORF) of BmOSC consists of 2,292 bp, encoding 764 amino acid residues with an apparent molecular mass of 87.62 kDa and theoretical pI 6.21. It contained four QxxxxxW motifs, one Asp-Cys-Thr-Ala-Glu (DCTAE) motif which is highly conserved among the triterpene synthases and another MWCYCR motif involved in the formation of triterpenoid skeletons. The deduced amino acid sequence of BmOSC shares 80.5 % & 71.8 % identity and 89.7 % & 83.5 % similarity with Olea europaea mixed amyrin synthase and Panax notoginseng dammarenediol synthase respectively. Phylogenetic analysis revealed that BmOSC is closely related with other plant OSCs. Quantitative real-time PCR (qRT-PCR) data showed that BmOSC is expressed in all tissues examined with higher expression in stem and leaves as compared to roots and floral parts.